Analysis Semiotic of Meaning Courage in Qaṣīdah (al-Burdah, al- Niffarīyah, al-Mutanabbī, and al-Ahtyar) - Sarah, Sarah; Amelya, Asy Syifa Reza; Sopian, Asep; Pauzi, Miftah (STIQ Amuntai, 2024)
This study aims to analyze the semiotic meaning of the word